The Combination Effect of Bean Sprouts Extract Concentration with Coconut Water on the Growth of the Density of Chlorella sp - Pratama, Dimas Oky; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Jurnal Perikanan dan Kelautan, 2024)
Chlorella sp is a kind of phytoplankton used as a natural food source for zooplankton, such as fish larvae and shrimp. Chlorella sp contains various nutrients that are good for the growth of fish larvae and shrimp. The success in cultivating Chlorella sp is closely related to the nutrient content at the time of cultivation. One alternative cultivation of Chlorella sp is using bean sprout extract and coconut water as the medium. Bean sprouts and coconut water extract can be used as a substitute for inorganic fertilizers. This research aims to determine the effect of bean sprout extract and coconut water on the growth of the density of Chlorella sp, as well as grasping the best dose that can be used to cultivate Chlorella sp. This research was conducted in July 2022 at the Aquaculture Environmental Quality Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This research used a one-factor, Completely Randomized Design (CRD) with four treatments and three replications. The treatments as defined in this research were P0 (Walne fertilizer 1 mL/L as control), P1 (8% bean sprout extract + 10% coconut water), P2 (10% bean sprout extract + 12.5% coconut water) and P3 (bean sprout extract 12% + coconut water 15%). These results indicate that P3 (12% bean sprout extract + 15% coconut water) is the best treatment for the growth of Chlorella sp with a density of 1091.00 x104 cells/mL and a specific growth rate of 0.9607 sel/mL, which occurred on the sixth day.